PENGARUH PROFITABILITAS, FINANCIAL LEVERAGE DAN ACID TEST RATIO TERHADAP DIVIDEN TUNAI PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2010 - Eva Susanti (Jurnal Akuntansi Muhammadiyah (JAM), 2012)
The purpose of this study was to examine the influence of profitability, financial leverage and the acid test ratio, either simultaneously or partially on dividends in cash on basic industries and chemical companies listed in Indonesia Stock Exchange. This study population amounted to 36 companies, with the observation period of 2008-2010. Because of all the elements of the studied population, the census method used in this study and the methods of analysis used multiple linear regression analysis.The results of this study indicate that either simultaneously or partially profitability, financial leverage and the acid test ratio affects the cash dividend on the company base and chemical industries listed in the Indonesia Stock Exchange.Â Keyword: Profitability, Financial Leverage, Acid Test Ratio, cash dividends.